Analisis Potensi Energi Surya Untuk Alat Bioteknologi Penghasil Nata De Coco Dengan Memanfaatkan Limbah Air Kelapa - Dion Brian Hatimanis; Stieven N. Rumokoy; Christopel H. Simanjuntak; Maureen Langie; Daisy D. G. Pangemanan; Herotje Siwi; Fridly Manawan (Jurnal Elektrik, 2024)
Coconut water (Cocos nucifera. L) has the potential to become a useful nata de coco product by utilizing biotechnology tools. Research conducted on "Analysis of Solar Energy Potential for Biotechnology Tools to Produce Nata de Coco by Utilizing Coconut Water Waste in North Sulawesi". The objectives of the research are as follows : to analyze the potential of solar energy for biotechnology tools to produce nata de coco by utilizing waste coconut water. The research method used by the author uses research and development (R&D) methods. It is a method or step in creating new products or developing and improving existing products and is used to test product effectiveness. This research can utilize discarded coconut water and can also develop biotechnological tools to produce nata de coco. The results of this research can be an illustration and input for readers regarding the factors of using solar energy for biotechnology tools to produce nata de coco using coconut water waste. The measurement results obtained are the average intensity value received by solar sell which is 146056 lux. So the average value of voltage consumption is: 12.21 volts, current: 22.45 amperes, power: 290 watts.